“Brilliantreflect”: smart mirror for smart life - Shelena Soosay Nathan; Amelia Sulaiman; Aisha Amila Kamarulzaman; Felicia Tiera; Mazniha Berahim (Institute of Advanced Engineering and Science, 2019)
In this globalization era, smart mirror have been one of the invention to represent futuristic interconnected physical object with several applications. Smart mirror is innovating appliance that incorporates with contextual information which offered the interactive user interface on the surface of a mirror with the use of Raspberry Pi 3. To create this smart mirror the methodology that includes analysis about smart mirror, designing the hardware and software, developing the prototype, implementation and lastly the evaluation phases needs to be take care of. The presentation performed on the mirror will be information such as weather, time and date, holiday calendar, to-do list by mobile synchronization, current traffic of selected area, news feed and compliment as a motivation. Furthermore, our framework also introduces music presentation that use for alarm purpose. In a nutshell, this mirror what we called “Brilliant Reflect” will be convenient to use as it provides various features to the user.